Separation Factor of Y/Dy Emulsion on Membrane Process Using Nitric Acid and D2EHPA Solvent - Kris Tri Basuki; Niken Siwi Pamungkas (Indonesian Journal of Chemistry, 2019)
Liquid extraction of Y that containing Dy using bis-2-Ethylhexyl phosphoric acid (D2EHPA) extractant has been conducted. The purpose of this study is to determine the optimum parameter in a separation process that uses membrane emulsion. As the aqueous phase, a mixed solution of Y2O3 and Gd2O3 containing Y 10 g/L and Gd 250 mg/L was used. D2EHPA as extractant or organic phase with a variety of concentration was diluted with kerosene. Emulsifier Span-80 was used to make an emulsion of membrane liquid. The internal phase of the liquid membrane used 0.20–0.50 M nitric acid, and the external phase used 1–5 M nitric acid. The studied parameters were extractant concentration, stirring speed, stirring time, and the ratio of the internal and external phase. X-Ray Fluorescence (XRF) was used for the analysis of Y and Dy. The analysis of Y and Dy used the X-Ray Fluorescence (XRF). The optimization results of the extraction process of Y with emulsion membrane using D2EHPA extractants obtained the following conclusions: the optimum stirring rate was 8500 rpm, the D2EHPA concentration was 4.5% in kerosene, the internal concentration was 0.45 M nitric acid, the external concentration was 4 M nitric acid, the stirring time was 10 min that fixed stirring rate was 500 rpm, and the ratio of internal and external phase was 1:1. This conditions acquired a separation factor (SF) Y-Gd of 7.57.